Manajemen Kurikulum Integratif antara Sekolah Alam dan Pondok Pesantren - Endang Rahma Sofaatin; Mada Sutapa (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the management of an integrative curriculum between nature-based schools and Islamic boarding schools (pesantren) as a holistic educational model that combines ecological and religious values. The research employed a descriptive qualitative approach using a case study method conducted in two educational institutions in Bondowoso over six months. The research subjects included principals, teachers, ustadz, students, and parents selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and document analysis of curricula and evaluation records. Data analysis utilized the interactive model of Miles and Huberman (2014), encompassing data reduction, data display, and conclusion drawing, with validity ensured through source, technique, and time triangulation. The findings indicate that curriculum planning is carried out collaboratively, implementation integrates nature-based learning with worship habituation, and evaluation emphasizes the balance of cognitive, affective, and spiritual aspects. This integrative model demonstrates effectiveness in fostering creative, independent, environmentally conscious, and religiously grounded learners. The study contributes to the development of alternative curriculum models that promote spiritual and ecological balance in Indonesian education.